A Facial Image Analysis based Algorithm to Detect Human Personality - Tauseef, H.; Shafique, S.; Fahiem, M.A.; Farhan, S. (The Nucleus, 2017)
Human personality plays an essential role in many fields of life. Facial features are used for, but are not limited, to different face recognition, pain detection, spontaneous and non-spontaneous action detection and personality detection systems. The main objective of this study is to judge human personality through facial features. Normalized facial images are used as an input. Interest points and features are extracted using Convolution Neural Network and distance metrics. Human personality is predicted using rule based classification. An accuracy of 84% for personality prediction with 8 fold cross validation is achieved.